2010
DOI: 10.1517/17425251003674364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary factors on levodopa pharmacokinetics

Abstract: An understanding of the pharmacokinetics of any drug is crucial for the establishment of its optimal therapeutic regimen, but this assumes a special importance with levodopa, due to its extensive presystemic metabolism, rapid absorption in the proximal small intestine and short plasma half-life. Major problems with levodopa treatment are the fluctuations in clinical response experienced in patients with advanced Parkinson's disease that sometimes are related to the peripheral pharmacokinetics of levodopa. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Salicylic acid has been shown to facilitate the absorption of levodopa after rectal administration in rats by a mechanism that requires its presence in the rectal membrane [ 38 ]. Studies have shown that exogenous administration of ascorbic acid improves levodopa absorption ( C max and AUC) in PD patients with poor levodopa bioavailability [ 39 , 40 ]. Therefore, one may speculate that tartaric acid cumulatively extends the window of levodopa absorption in the gastrointestinal tract by promoting an acidic milieu in regions of the intestine where levodopa is a substrate for pH-sensitive amino acid transporters or exchangers, by inhibiting P-gp-mediated efflux from the more distal regions of the intestine or by enhancing its mucosal permeation via paracellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Salicylic acid has been shown to facilitate the absorption of levodopa after rectal administration in rats by a mechanism that requires its presence in the rectal membrane [ 38 ]. Studies have shown that exogenous administration of ascorbic acid improves levodopa absorption ( C max and AUC) in PD patients with poor levodopa bioavailability [ 39 , 40 ]. Therefore, one may speculate that tartaric acid cumulatively extends the window of levodopa absorption in the gastrointestinal tract by promoting an acidic milieu in regions of the intestine where levodopa is a substrate for pH-sensitive amino acid transporters or exchangers, by inhibiting P-gp-mediated efflux from the more distal regions of the intestine or by enhancing its mucosal permeation via paracellular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While some dietary patterns focus on the distribution of different food groups in an individual’s diet, other dietary patterns focus on the distribution of macronutrients, such as protein. Previous research linked dietary protein to levodopa bioavailability based on both substances utilizing the same large neutral amino acid transporter for absorption in the small intestine and transport across the blood–brain barrier [ 85 , 86 , 87 ]. The purpose of a PRD is to improve the bioavailability of levodopa by limiting protein consumption [ 87 , 88 ].…”
Section: Protein-restricted Dietmentioning
confidence: 99%
“…Intake of levodopa with foods, the time of ingestion of a meal, fat, fiber, ascorbic acid may change the effectiveness of drug in the body (Fernandez et al 2010). Patients receiving levodopa treatment should be monitored for food intake with the drug, carbohydrate and protein content of the meals, and associated micronutrient deficiencies.…”
Section: Dopaminergic Agentsmentioning
confidence: 99%